The relationship between economic growth, oil production, energy consumption and carbon dioxide emissions: Evidence from selected OPEC countries - Anh Tru Nguyen (Journal of Contemporary Economic and Business Issues, 2020)
The article aims to investigate the relationship between economic growth, oil production, energy consumption and CO2 emissions in five OPEC countries for the last four decades (1978-2017). We found that per capita energy consumption has a negative relationship with per capita GDP while per capita CO2 emissions positively affect per capita GDP. Per capita GDP negatively affects oil production, but per capita energy consumption has a positive relationship with oil production. Further, per capita CO2 emissions have a positive relationship with oil production. Per capita energy consumption negatively influences per capita CO2 emissions. We also found that there is a directional relationship running from per capita GDP to oil production, per capita energy consumption and per capita CO2 emissions and from per capita CO2 emissions to per capita energy consumption. The Johansen co-integration test shows that there is a long run relationship among variables. Our finding supports the conservation hypothesis that means the growth of GDP in these countries is found as a result of increasing energy consumption.
Keywords: O11; O47; Q43; 330; Economic Growth; Oil Production; Energy Consumption; Carbon Dioxide Emission; OPEC